2009
DOI: 10.1177/0883073809334383
|View full text |Cite
|
Sign up to set email alerts
|

Is Hyperventilation an Effective ‘‘Activating’’ Procedure in Routine Clinical EEG Studies in Children?

Abstract: Electroencephalography (EEG) records of consecutive 275 children (ages 3-18 years; average 11 years; 34.5% females), with generalized epilepsy, consistent with epileptiform discharges in baseline EEG, who underwent 5 minutes of voluntary hyperventilation during standard EEG recordings were reviewed in this study to determine the actual value of the voluntary hyperventilation in routine clinical EEG in provoking epileptiform EEG abnormalities. Of the 275 EEG records, only in 11.6% hyperventilation revealed incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
2
9
1
Order By: Relevance
“…Another interesting brief communication of Raybarman 20 showed that from 275 recorded pediatric patients with generalized epilepsy, in only a small amount of them (11.6%) the HV maneuver induced an increase of interictal epileptiform discharges, and none of them had clinical seizures induced during HV. The value of hyperventilation as an ‘‘activating’’ procedure in routine clinical EEG studies was questioned in this study even in generalized epilepsies.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting brief communication of Raybarman 20 showed that from 275 recorded pediatric patients with generalized epilepsy, in only a small amount of them (11.6%) the HV maneuver induced an increase of interictal epileptiform discharges, and none of them had clinical seizures induced during HV. The value of hyperventilation as an ‘‘activating’’ procedure in routine clinical EEG studies was questioned in this study even in generalized epilepsies.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperventilation is the oldest provocation methods, its efficiency in triggering absence seizures being observed even before the use of EEG, while the effect it has on cerebral electric activity has been observed by Berger in 1934 and further studied by Gibbs et al in 1935. [15][16][17] Over time, its diagnostic value has been certified by several studies and it has become a part of most standard EEG recordings [16][17][18][19][20][21][22][23][24][25] and it is also of use in intracranial EEG recordings 26 .…”
Section: Introductionmentioning
confidence: 99%
“…As a provocation method, it has proven to be more useful in generalized epilepsy, and especially in absence seizures 16,17,[19][20][21][27][28][29] , but also in Juvenile Myoclonic Epilepsy [29][30][31] . Nevertheless, some studies have shown that it can also trigger focal seizures, especially those with a temporal lobe onset 17,22,23,26,28 while others question its value for focal epilepsy 18,24,27 In addition to epileptiform discharges, HV can also elicit slow activity. Sometimes this is a normal phenomenon, especially in children or young adults, but it can also point to a specific cerebral disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations